Hydractinia angusta Hartlaub 1904 - Peña Cantero, Álvaro L. (Zenodo, 2015)
Hydractinia angusta Hartlaub, 1904 (Fig. 7 A–H) Hydractinia angusta Hartlaub, 1904: 7, pl. 4, figs 1–7; Totton, 1930: 138; Peña Cantero & Ramil, 2006: 950 –951, fig 2; Peña Cantero, 2004: 768; 2014b: 1714. ? Hydronema angustum — Briggs, 1938: 10. Halorhiza angusta — Stechow, 1962: 418. ? Hydractinia angusta — Naumov & Stepanjants, 1972: 33, 35, fig 1; Stepanjants, 1979: 13, pl. 1, fig 7; Cerrano et al ., 2000: 488 –493, figs 2–5; 2001: 577–580; Galea & Schories, 2012: 2, pl. 1A–E, fig 2A–C; Peña Cantero et al . 2013: 737 –739, figs 3g –h, 4a–c. Material examined. Belgica Antarctic Expedition 1897–1899: labelled “cotype” (RBINS 539798 INV 38500), (nº 1059), 28.V.1898, 71°19' S, 87°37' W (Bellingshausen Sea), 400 m, c. 22-mm-long colony fragment, with gonophores. Description. Colony growing along three sponge spicules, forming a sort of cylinder of perisarc filled with coenosarc; structure very soft. Polyps white. Gastrozooids and gonozooids present. No dactylozooids. Gastrozooids of varied size (longest c. 1 mm, usually smaller, between 330 and 390 µm) and with eight to ten filiform tentacles arranged in a crown near the middle of the polyp (Fig. 7 A–C). Hypostome relatively large, finger-shaped (Fig. 7 A–C). Gonozooids much smaller, from 140 to 250 µm high, and provided with up to six filiform tentacles (Fig. 7 D– G); gonozooids with fewer tentacles or even completely devoid of tentacles also present. Gonozooids with up to five tiny (from 50 to 70 µm in diameter), rounded gonophores at base (Fig. 7 D–G). Some blunt spines present (Fig. 7 H). Measurements (in µm). Cnidome : Type I [range 7.0–10.0 x 2.0–3.0, mean 8.6±1.0 x 2.7±0.5 (n=10); ratio, range 2.3–4.0, mean 3.3±0.6 (n=10)], Type II [range 11.0–15.0 x 2.5–4.0, mean 12.7±1.4 x 3.5±0.6 (n=6); ratio, range 2.8–4.8, mean 3.8±0.9 (n=6)], desmonemes [range 5.0–6.5 x 2.0–2.5, mean 5.8±0.5 x 2.2±0.2 (n=5); ratio, range 2.4–3.3, mean 2.7±0.3 (n=5)]. Remarks. I have only examined part of the material studied by Hartlaub (1904), in particular the c. ...